Effect of cyclic torsional preloading on cyclic fatigue resistance of ProTaper Next and Mtwo nickel-titanium instruments - Eugenio Pedullà; Fabio Lo Savio; Gianluca Plotino; Nicola Maria Grande; Silvia Rapisarda; Gianluca Gambarini; Guido La Rosa (Ariesdue, 2015)
Aim: To evaluate the influence of different torsional preloads on cyclic fatigue resistance of endodontic rotary instruments made by conventional nickel-titanium (NiTi) or M-Wire. Methods: Eighty new Mtwo (#25/0.06) (Sweden & Martina, Due Carrare, Padova, Italy) and ProTaper Next X2 (Dentsply Maillefer, Ballaigues, Switzerland) were used. The Torque and distortion angles at failure of new instruments (n = 10) were measured and 0% (n = 10), 25%, 50%, and 75% (n = 20) of the mean ultimate torsional strength as preloading condition were applied according to ISO 3630-1 for each brand. The twenty files tested for every extent of preload were subjected to 25 or 50 torsional cycles (n = 10). After torsional preloading, the number of cycles to failure was evaluated in a simulated canal with 60° angle of curvature and 5 mm of radius of curvature. Data were analyzed using 2-way analysis of variance. Scanning electron microscope (SEM) was performed to evaluate the fracture surface of each fragment. Results: ProTaper Next X2 reduced their cyclic fatigue after 25 or 50 cycles of every torsional preloading (25%, 50%, and 75%) (P < 0.01). Cyclic fatigue of Mtwo was reduced by 50 cycles of every torsional preloading and only after the 75% of preload for 25 cycles (P < 0.01). Conclusions: Torsional preloads reduced the cyclic fatigue resistance of M-wire and conventional (as ProTaper Next and Mtwo) NiTi rotary instruments except for Mtwo with 25% or 50% of torsional preloading.